Seroprevalensi Virus Egg Drop Syndrome pada Bebek Petelur di Kecamatan Negara, Kabupaten Jembrana, Provinsi Bali (SEROPREVALENCE OF EGG DROP SYNDROME VIRUS IN LAYER DUCKS IN NEGARA DISTRICT, JEMBRANA REGENCY, BALI PROVINCE) - Kencana, Gusti Ayu Yuniati; Kardena, I Made; Puspitayani, Putu Mira (Jurnal Veteriner; Vol 20 No 2 (2019), 2019)
A study was conducted to determine disease seroprevalence of egg drop syndrome (EDS) virus in layer ducks in Negara district, Jembrana, Bali. A total of 180 samples of laying duck serum with different management systems were used in this research. A number of 90 serum out of 180 samples were taken from ducks with an extensive management system (reared in the ricefield), and 90 other serum samples were taken from intensive ducks (caged) from community farms in six  villages randomly taken from Nagara districts. Serum sampel were collected from EDS un-vaccinated ducks. Serum samples were tested using an hemagglutination/inhibition test (HA/HI test). Data were analyzed using chi-quadrat analysis (X2). The results showed that duck layers maintained in n Negara district had EDS antibody titer of 23 to 29 HI units. The results showed that  68 (75.56% ) of layer ducks with an extensive management system have EDS antibody titer, whereas  only 18 (20%) of layer ducks with an intensive management system have EDS antibody titer. This indicates layer ducks in both management systems have antibody to EDS virus without EDS vaccination and that the layer ducks reared in ricefield has higher seroprevalence percentage than layer ducks reared in intensive cages.